Boys: their Work and Influence - Anonymous (Salt Lake City, UT : Project Gutenberg, 2007)
"Boys: their Work and Influence" by Anonymous is a guidebook aimed at young boys in the working classes, likely written during the late 19th century. The book addresses the responsibilities and potential of boys as they transition from childhood to adulthood, emphasizing character development, moral integrity, and the importance of work in shaping their futures. The content of the book covers a wide array of topics relevant to young boys, including their duties at home and school, the importance of education, religious practices, and the moral implications of friendships and courtship. It encourages boys to embrace their capabilities while warning them against common pitfalls associated with adolescence, such as peer pressure and the allure of dishonesty. The author aims to aid young boys in forming strong moral character that will guide them into becoming responsible, God-fearing men, equipping them with the tools necessary to navigate the complexities of life with integrity and purpose. Throughout, the book combines practical advice with moral teachings, reinforcing the idea that hard work and ethical behavior are essential for personal success and societal contribution. (This is an automatically generated summary.)
Release date is 2007-10-28
Transcribed from the Skeffington & Son tenth edition by David Price
Keywords: Christian life; Boys -- Conduct of life